A simple implementation of a low power-factor wattmeter. (December 2021) - Slomovitz, Daniel; García, Ricardo; Faverio, Carlos; Trigo, Leonardo
Abstract: This paper presents a new implementation of a wattmeter based on the adding principle. Its major advantages are the very high accuracy it can reach at low power factor measurements, and the simple construction. Although the measuring method is well known, this work proposes to join analogue devices with a digital voltmeter (DMM) to get a new implementation. We use a simple switch and a binary inductive divider to implement the addition and subtraction, which practically cancels the errors due to this operation. Additionally, as the same DMM is used for measuring both conditions, its errors vanish at null power factor because the voltage is the same in both cases.